The day-night differences in ERK1/2, GSK3β activity and c-Fos levels in the brain, and the responsiveness of various brain structures to morphine - Bendová, Zdeňka; Pačesová, Dominika; Novotný, Jiří (Journal of comparative neurology, 2020)
As with other drugs or pharmaceuticals, opioids differ in their rewarding or analgesic effects depending on when they are applied. In the previous study, we have demonstrated the day/night difference in the sensitivity of the major circadian clock in the suprachiasmatic nucleus to a low dose of morphine, and showed the bidirectional effect of morphine on pERK1/2 and pGSK3β levels in the suprachiasmatic nucleus depending on the time of administration. The main aim of this study was to identify other brain structures that respond differently to morphine depending on the time of its administration. Using immunohistochemistry, we identified 44 structures that show time-of-day specific changes in c-Fos level and activity of ERK1/2 and GSK3β kinases in response to a single dose of 1 mg/kg morphine. Furthermore, comparison among control groups revealed the differences in the spontaneous levels of all markers with a generally higher level during the night, that is, in the active phase of the day. We thus provide further evidence for diurnal variations in the activity of brain regions outside the suprachiasmatic nucleus indicated by the temporal changes in the molecular substrate. We suggest that these changes are responsible for generating diurnal variation in the reward behavior or analgesic effect of opioid administration.
Keywords: Male; Rats, Wistar; Brain; Morphine; Analgesics, Opioid; Glycogen Synthase Kinase 3 beta; mužské pohlaví; potkani Wistar; opioidní analgetika; cirkadiánní rytmus; MAP kinasový signální systém; Circadian Rhythm; krysa rodu Rattus; MAP Kinase Signaling System; Animals; morfin; zvířata; Rats; mozek; Proto-Oncogene Proteins c-fos; protoonkogenní proteiny c-fos; kinasa glykogensynthasy 3beta